(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Due to the increasing production of modern explosive-resistant vehicles, materials, and equipment, the calls for improved energetic materials (EMs) with a more destructive energetic capability and high thermal stability for engineering and warfare have received tremendous attention from researchers. Weka version 3.8.5 machine learning software has been used in this research to carry out the accurate energetic velocities predictions and to develop and generate five (5) novel models from the seventy-one (71) experimental EM compounds. Also, the quantitative structural property relationship (QSPR) method was used to design five (5) new EM along with their new energetic velocities (EV) of 10.835 Km/s, 10.22 Km/s, 10.531 Km/s, 10.436Km/s, and 10.33Km/s. The energetic velocities of all the five newly designed EMs were better than those reported in the literature and also better than the standard energetic compounds, TNT. Because of their unique energetic properties, The energetic compounds such as N, N’-(3,6 dinitropyrazolo[4,3-c]pyrazole-1,4-diyl)bis(N-fluoronitramide) should be given special consideration while synthesizing those compounds. Furthermore, the results of this research have proven the scientific importance of using QSPR as a research tool in the field of energetic materials